2022
DOI: 10.3390/plants11243579
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Stress and Long-Read cDNA Sequencing of Sunflower (Helianthus annuus L.) Revealed the Origin of the Plant Retrotranscriptome

Abstract: Transposable elements (TEs) contribute not only to genome diversity but also to transcriptome diversity in plants. To unravel the sources of LTR retrotransposon (RTE) transcripts in sunflower, we exploited a recently developed transposon activation method (‘TEgenesis’) along with long-read cDNA Nanopore sequencing. This approach allows for the identification of 56 RTE transcripts from different genomic loci including full-length and non-autonomous RTEs. Using the mobilome analysis, we provided a new set of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previous investigations claimed that plants grown on ZA media and subjected to stress, such as heat stress, are stimulated to produce eccDNAs [10,17]. We combined epigenetic (ZA) stress with each of the following stimuli to detect stress-responsive eccDNA loci: heat stress (HS), flagellin treatment (Flg), and abscisic acid treatment (ABA).…”
Section: Detection Of Eccdnas Under Abiotic Hormone and Flagellin Tre...mentioning
confidence: 99%
“…Previous investigations claimed that plants grown on ZA media and subjected to stress, such as heat stress, are stimulated to produce eccDNAs [10,17]. We combined epigenetic (ZA) stress with each of the following stimuli to detect stress-responsive eccDNA loci: heat stress (HS), flagellin treatment (Flg), and abscisic acid treatment (ABA).…”
Section: Detection Of Eccdnas Under Abiotic Hormone and Flagellin Tre...mentioning
confidence: 99%
“…However, the utilization of this method in other plant species has not been sufficiently demonstrated. Recently, TEgenesis was applied to reactivate TEs in sunflowers [55]. The authors demonstrated the induction of expression for 16 TE-related loci, and ten of them also showed copy number variation between sunflower varieties, indicating transposition potential.…”
Section: Controlled Activation Of Tes Via Polii and Dna Methylation I...mentioning
confidence: 99%
“…Before the broad creation and application of iTE collections, several obstacles must be resolved. First, the developed TEgenesis approaches seem to be very harmful for plants, reducing the plant survival rate [55]; therefore, alternative approaches need to be developed to ensure TEI occurrence in germline plant cells, enabling the genetic inheritance of novel TEIs. Second, the number of active TEs for which the triggering factor is known is extremely low.…”
Section: Challenges and Emerging Perspectives Of Te-mediated Biologic...mentioning
confidence: 99%